Inclusion in agri-food systems in Bangladesh: the digital innovation and transformation initiative - Sarker, F.; Mamun, K. A.; Uddin, J.; Ahmed, S.; Nisha, N. A.; Joshi, Deepa (International Water Management Institute (IWMI). CGIAR Initiative on Digital Innovation, 2023)
Agriculture has played a crucial role in supporting smallholder livelihoods in Bangladesh. Despite being actively involved in various stages of production, including seed sowing, harvesting, and postharvesting, women's contributions are often undervalued. They are often regarded as a cheap labor force and are not given meaningful roles in the supply and value chains. One of the primary challenges they face is the lack of access to and ownership of land, which results in limited and unequal access to resources such as credit, services, markets, and information on modern technologies. These disparities hinder women's participation in market systems and further widen gender gaps and digital divides. Studies have shown that Bangladesh has one of the highest gender gaps in mobile internet usage among low and middle-income countries. This study examines the gender digital divide in Bangladesh, focusing on the reasons behind women's exclusion from digital information highways and their limited access to, use of, and benefits from internet-based agriculture and climate-related services and innovations. In addition to a comprehensive review of secondary data, we conducted a needs-based assessment using both quantitative and qualitative indicators in three divisions. Qualitative data were collected through focus group discussions, in-depth interviews, and key informant interviews. Both the qualitative and quantitative studies shed light on the social, economic, and contextual issues related to the digital ecosystem in the agriculture sector. The assessment also evaluates the effectiveness of public, private, and civil society interventions in the study areas. Our findings reveal that most digital initiatives fail to address the economic gaps and challenges faced by smallholder farmers, poor women, and rural youth. To address these challenges and promote gender equality in agriculture, it is crucial for the government to implement consistent policies across government agencies and develop strategies that prioritize closing digital divides in the agricultural sector.